Ethno-botanical and microbiological analysis of selected endangered medicinal plants of Karnataka - VANI L; DR. M.JAYARAMU (International Journal of Pharma and Bio Sciences, 2019)
Ethnobotanical reports suggested the presence of several numbers of medicinally important plant-species from all over the world containing a high degree of curative properties against pathogens. The current onus is on researching and developing new antimicrobial agents from various sources to combat microbial resistance build up among pathogens. The current investigation is on the antimicrobial properties of the endangered medicinal plants chosen from the region of Karnataka, India. project investigations have been carried out to test the presence of the antimicrobial compounds present in the parts of the following plants - Janakia arayalpathra , Artocarpus hirsutus, Calophyllum apetalum Wild., Terminalia orenulata, Dorstenia indica and Vernonia amygdalina. The dried extracts of flowers, leaves and stem of the endangered plants were analysed for their antimicrobial properties using well diffusion method and the minimum inhibitory concentration (MIC) of the extracts showing positive inhibitory activity against pathogens like E. coli, E. faecalis, S. aureus and K. pneumoniae. The results indicated that the plant flower, leaf and stem extract of Vernonia amygdalina possess antimicrobial property with a zone of inhibition measuring 7 to 10 mm against E.coli and E.faecalis. The plant Wild jack or Artocarpus hirsutus showed antimicrobial property which were restricted to its stem extract against E. faecalis only. While Janakia arayalparthra showed a positive antimicrobial activity against S. aureus only.